2010
DOI: 10.1080/15287394.2010.511553
|View full text |Cite
|
Sign up to set email alerts
|

Ceramide Produces Apoptosis Through Induction of p27kip1by Protein Phosphatase 2A-dependent Akt Dephosphorylation in PC-3 Prostate Cancer Cells

Abstract: Ceramide induces cell cycle arrest and apoptotic cell death associated with increased levels of p27(kip1). The aim of this study was to examine the effects of ceramide on p27(kip1) protein levels as a measure of cell cycle arrest and apoptosis. Results showed that ceramide increased p27(kip1) protein levels through activation of protein phosphatase 2A (PP2A) in PC-3 prostate cancer cells. Treatment of cells with the PP2A inhibitor okadaic acid or with PP2A-Cα siRNA inhibited ceramide-induced enhanced p27(kip1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 39 publications
2
30
0
Order By: Relevance
“…Akt can regulate the cell cycle by enhancing the transcription of cell cycle regulators and modulating their stability directly or indirectly through phosphorylation on specific sites (16,(27)(28)(29). Consistent with the previous study, we observed that ASA induced HepG2 cell accumulation in the G0/G1 phase.…”
Section: Discussionsupporting
confidence: 82%
“…Akt can regulate the cell cycle by enhancing the transcription of cell cycle regulators and modulating their stability directly or indirectly through phosphorylation on specific sites (16,(27)(28)(29). Consistent with the previous study, we observed that ASA induced HepG2 cell accumulation in the G0/G1 phase.…”
Section: Discussionsupporting
confidence: 82%
“…Use of ceramide to treat PC-3 human prostate cancer cells revealed that ceramide-activated PP2A dephosphorylates phospho-Akt (25). In this study, we found that OA reversed YBBEs-mediated downregulation of p-PI3K, p-Akt and p-MDM2, suggesting that targeting PP2A may be a feasible way to affect the pivotal stage.…”
Section: Discussionmentioning
confidence: 51%
“…For instance, de novo ceramide generation was found to be important for triggering apoptosis specifically in melanoma cells as evidenced by the lack of apoptosis when serine palmitoyltransferase activity is blocked [42]. However in prostate cancer cancer cell lines, ceramide-mediated apoptosis appeared to be driven by Akt dephosphorylation through protein phosphatase 2A activity [43]. Similarly, in another study, ceramide analogs were shown to induce apoptosis by affecting mitochondria along with the concomitant dephosphorylation of Akt [44].…”
Section: Cellular Roles Of Bioactive Sphingolipidsmentioning
confidence: 97%